PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA DENGAN LINGKUNGAN KERJA SEBAGAI VARIABEL MODERASI (PADA KARYAWAN BALAI PENELITIAN TANAMAN PEMANIS DAN SERAT MALANG) - Firdian, Cici (Manajemen Bisnis, 2017)
The purposes of this research are, first, is to describe culture organization, work environment and employee performance at Balai Peneletian Tanaman Pemanis dan Serat Malang. Second know whether work environment moderating significant impact culture organization of the performance of employees at Balai Peneletian Tanaman Pemanis and Serat Malang. Sample in this research are employees of administration 40 respondents. Technique data collection using interviews, the questionnaire and documentation. Instrument the analysis used in this research using range the scale and Moderated Regression Analysis (MRA). The results of the analysis range scale culture organizations including on the criteria strong , work environment including on the criteria conducive and performance including the high criteria. The results of the analysis MRS said environment moderating significant impact culture organization of the performance of employees Balai Peneletian Tanaman Pemanis and Serat Malang.